Scheme Design and Key Technology Application of Multi-joint Unmanned Underwater Vehicle - HAN Tao; HU Zhiqiang; CUI Qingjia; QING Xiaohui; XU Biao (Kongzhi Yu Xinxi Jishu)
Concerning the challenges of limited operational capabilities of autonomous underwater vehicles and the impaired passability caused by the externally mounted propellers on the existing chained multi-body underwater vehicles, this paper presents an overall design scheme for a multi-joint unmanned underwater vehicle composed of a functional carrier and a basic carrier. Initially, the structural arrangements of the functional carrier and basic carrier are introduced. Subsequently, a comprehensive exploration of the key technological principles incorporated in the scheme, such as jet manipulation, vector propulsion, folding antennas, among others is conducted. Lastly, a physical prototype of the basic carrier for the multi-joint unmanned underwater vehicle is developed, followed by successive trials in lake and sea environments. In the directional variable depth navigation tests, the depth error was no more than ±0.1 m, and the heading error was not exceeding ±1°. These experiment results validate the sailing capabilities of the basic carrier of the multi-joint unmanned underwater vehicle, thereby confirming the feasibility of the proposed design scheme for a multi-joint unmanned underwater vehicle in this paper.